2006
DOI: 10.1088/0953-8984/18/46/006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal phase behaviour ofN-alkyl-N-methylpyrrolidinium and piperidinium bis(trifluoromethanesulfonyl)imide salts

Abstract: The phases, ion crystal packing and thermal properties of the N-alkyl-N-methylpyrrolidinium and piperidinium bis(trifluoromethanesulfonyl)imide (PYR1RTFSI and PIP1RTFSI (subscript R = 1 for methyl and 2 for ethyl), respectively) salts are compared using powder and single-crystal x-ray diffraction (XRD) and differential scanning calorimetry (DSC). The crystal structure of PIP12TFSI has been determined at 123 K. The salt crystallizes in the triclinic space group with Z = 8. Structural data are also reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…48 In some cases, most notably ͓Pyrr 14 ͔ + / ͓NTf 2 ͔ − , crystals formed far from equilibrium are metastable with respect to annealed ones and they melt at lower temperatures. 49 Elegant work by Endo and coworkers 50,51 using very sensitive and slow DSC scanning, coupled with Raman spectroscopy, have shown that the dynamics of cooperative change between side chain conformers complicate the crystallizing and melting processes, contributing to the complex thermal behaviors of ILs.…”
Section: Thermal Properties Of Ilsmentioning
confidence: 99%
“…48 In some cases, most notably ͓Pyrr 14 ͔ + / ͓NTf 2 ͔ − , crystals formed far from equilibrium are metastable with respect to annealed ones and they melt at lower temperatures. 49 Elegant work by Endo and coworkers 50,51 using very sensitive and slow DSC scanning, coupled with Raman spectroscopy, have shown that the dynamics of cooperative change between side chain conformers complicate the crystallizing and melting processes, contributing to the complex thermal behaviors of ILs.…”
Section: Thermal Properties Of Ilsmentioning
confidence: 99%
“…The ionic volumes of the unsymmetrical tetraalkylphosphonium cations, C n (C m ) 3 P + , were calculated in this work from the few values for individual lengths of the alkyl chains [3,5,6,10,19,20]. A few individual cationic volumes, not covered by these expressions are: 1-butyl-2,3-dimethylimidazolium (C 4 mmim + ) [17], 1-butyl-4-methylpyridinium (C 4 (4 M)Py + ) [6], and 1-ethyl-1-methylpiperidinium (EtMePip + ) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the interest of new ionic liquids (ILs) as alternatives for conventional organic solvents is increasing to the pyrrolidinium-based ILs [1][2][3][4][5] and piperidinium-based ILs [6][7][8][9][10][11][12][13][14]. The pyrrolidinium-based ILs were used in biological synthesis as catalysts [2], in chemical capacitors [3] and in the preparation of a novel class of polymer electrolytes based on polymer-ionic liquid gels [4].…”
Section: Introductionmentioning
confidence: 99%
“…The 1-ethyl-1-methylpiperidinium bis{(trifluoromethyl)sulfonyl}imide, [EMPIP][NTf 2 ] and 1-ethyl-1-methylpyrrolidinium bis{(trifluoromethyl)sulfonyl}imide, [EMPYR][NTf 2 ] were compared with X-ray diffraction and differential scanning calorimetry (DSC) to show a highly endothermic solid-solid phase transition prior to fusion and to show the differences in ion crystal packing and the influence of the alkyl chain [8]. It was shown, that the high-temperature disordered phases present before melting are very similar for the piperidinium-based ILs and pyrrolidinium-based ILs, explaining the similar fusion temperatures for the analogous piperidinium and pyrrolidinium ILs [8]. High thermal stability, possible application in lithium-ion batteries 0378-3812/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%